Medical Image Computing and Computer-Assisted Intervention - MICCAI 2008 - Metaxas, D. (Springer, 2017)
The two-volume set LNCS 5241 and LNCS 5242 constitute the refereed proceedings of the 11th International Conference on Medical Image Computing and Computer-Assisted Intervention, MICCAI 2008, held in New York, NY, USA, in September 2008.